'Accident investigation in the wild' – A small-scale, field-based evaluation of the STAMP method for accident analysis. (February 2016) - Underwood, Peter; Waterson, Patrick; Braithwaite, Graham
Highlights: A mixed-methods practitioner-focused evaluation of STAMP was conducted. Practitioners analysed data collected in a simulated investigation with STAMP. Issues affecting the use of STAMP by practitioners are examined. Abstract: Little information is currently available about the application of systemic accident analysis methods by practitioners and whether their analysis needs are met. This study provides an insight into this issue by obtaining a practitioner evaluation of STAMP and understanding how the method's usage characteristics affect its use in a live investigation scenario. Six participants took part in a workshop to analyse data collected during a (high-fidelity, partly field-based) simulated investigation exercise using STAMP. The analysis outputs were assessed, along with the participants' questionnaire and focus group responses pertaining to their experiences of using the method. When combining the mixed methods data generated during the study, a number of observations regarding the participants' experiences of using STAMP were made. However, improving the method's usability and graphical output were highlighted as key developments that may improve its acceptance by practitioners.